Analisis Pendapatan dan Tingkat Kesejahteraan Rumah Tangga Petani Bawang Merah di Kelurahan Mataran Kecamatan Anggeraja Kabupaten Enrekang : Cofee Farmers - Nurhaedah, Nurhaedah; Irmayani, Irmayani; Ruslang, Ruslang; Jumrah , Jumrah (Jurnal Ilmiah Pertanian dan Peternakan, 2023)
Purpose: This study aims to analyze the income and welfare levels of shallot farmer households in Mataran Village, Anggeraja District, Enrekang Regency. Research Methodology: The research adopts a quantitative approach using observations, interviews, and structured questionnaires as data collection methods. The study was conducted from November to December 2022 with a population of 350 shallot farmer households. A sample of 35 farmers was selected randomly. The analysis focused on calculating production costs, revenues, income, and evaluating the welfare level of farmer households based on income-to-cost ratios. Results: The findings show that the total cost incurred by farmers was Rp. 863,594,343, while total revenue reached Rp. 1,936,200,000, resulting in an income of Rp. 1,072,605,657. The revenue-to-cost ratio was 2.24 > 1, indicating that shallot farming is profitable. Furthermore, the welfare analysis reveals that the majority of farmer households in the study area were categorized as prosperous, based on income levels and their ability to meet household needs. Conclusion: Shallot farming in Mataran Village provides significant profits and contributes positively to improving the welfare of farmer households. The high income-to-cost ratio highlights shallot cultivation as a viable agricultural livelihood in the region. Limitations: This study is limited to a small sample size of 35 respondents and only considers monetary indicators of welfare, excluding broader social and environmental factors. Contribution: The research provides empirical evidence on the profitability of shallot farming and its role in enhancing rural household welfare, serving as a reference for agricultural policy development and rural economic planning.